The current state of underground and superficial waters in the area of the liquidated mine Mgachi (Sakhalin island, Russia) - Tarasenko Irina; Zinkov Aleksandr (Федеральное государственное автономное образовательное учреждение высшего образования «Дальневосточный федеральный университет», 2014)
The article is concerned with the hydrogeochemical peculiarities of the underground waters of the liquidated mine Mgachi. It has been found that the mine being flooded, technogenic (mine) waters were produced in the exhausted rock mass, which contain hydrocarbonates, sulfates, sodium, iron, mineral oil, zinc, manganese, copper, and chrome exceeding the limits of tolerance. The mineralisation of the mine waters varies between 2.062 and 4.71 g/L. The estimation of the effect the mine waters have on the surface water channels reveals that the flooded mine pollutes considerably the rivers Malyi Sertunai and Rozhdestvenka.
Keywords: ЛИКВИДИРОВАННАЯ ШАХТА; LIQUIDATED MINE; POLLUTED UNDERGROUND WATERS; ВЛИЯНИЕ НА ПОВЕРХНОСТНЫЕ ВОДОТОКИ; EFFECT ON SURFACE WATER CHANNELS; ЗАГРЯЗНЕННЫЕ ПОДЗЕМНЫЕ ВОДЫ; 502.51 +504.61+553.94(571.64)